The placing of line surge arresters and fuses on 11 and 12 kV lines to protect equipment against lightning - Dirkse van Schalkwyk, W. J. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MEng)--University of Stellenbosch, 2001.